A New Spray Reagent for Identification of Amino Acids on Thin-Layer Chromatography Plates - Datta Samanta, Titil; Nag, Manaswita; Laskar, Subrata (Asian Journal of Chemistry, 2016)
Identification of amino acids is extremely important in evaluation of protein structure for determining their occurrence in the free state in numerous natural products and also for the determination of C-terminal units of degraded proteins. Several specific and non-specific reagents have been reported to identify amino acids on thin-layer chromatography plates. Among these, ninhydrin is the most popular due to its high sensitivity. However, ninhydrin produces the same purple/violet colour with most of the amino acids. A new spray reagent (2,3-dichloro-1,4-naphthoquinone) with high sensitivity for easy and rapid identification of amino acids on thin-layer plates has been introduced.